Relationship Of Intelligence With The Motor Growth Of Preschool Children - Sabir, Orenik (Journal of Physical Education, 2015)
The research aims to identify the relationship between the motor intelligence and motor growth of preschool children. Researcher assumed there is a significant association between motor intelligence and motor growth of preschool children. And used the theoretical studies and materials under study and has been used the descriptive approach in a manner of relations being it fits the nature of the research. And was selected sample of primer children from Balla kindergarten in Erbil province of the year 2014 - 2015 ages (5-6 years) were chosen intentionally as numbered (26) boys and girls and (12) child were excluded because the study was limited to male children and thus the final sample reached (14) child. Data has been processed statistically by using statistical package (SPSS). and Atantjt researcher Mayati: 1. The lack of significant correlation between motor development choices and choose drop the ball with the exception of choice (soft ball throw). 2. The lack of a significant correlation between motor development choices and choose lapping around the circle with the exception of the selection (running 20 m). 3. The absence of a significant correlation between motor development choices and select the sound and movement with the exception of the selection (the man right). One of the main recommendations: 1. Conduct a study similar to the female and the present study compared the results. 2. The need to focus on the sensory receptors to preschool because of its significant role in the dynamic development of intelligence. 3. The need for attention to the Games motor in pre-school, which contribute to raising the mental and motor efficiency for the kids